Pemodelan dan Implementasi Proses Bisnis Berbasis E-CRM Menggunakan Aplikasi VTiger CRM - I Putu Agung Bayupati; I Wayan Widiana; Putu Wira Buana (Ikatan Ahli Informatika Indonesia (IAII), 2020)
Good relationship between company and customers needs to be managed to maintain continuity of the company’s business considering that business competition is very competitive. CV. Tirta Tamanbali is industrial company that manufactures bottled water products located in Bali. Seeing existence of various competitor makes the company’s business processes gradually decline. Examples of decreased business processes experienced by companies that must be closed distributors outside the region. After conducting research, it was found several business processes related to customers that were still not optimally. Some of these business processes are marketing processes that are not carried out by companies, sales processes that have not been integrated where transactions that occur between companies and customers still utilize phones and supporting processes like complaints and questionnaire services that are still done manually and unscheduled. Based on these problems, the development of business processes starting from modeling stage to implementation is carried out by utilizing the E-CRM application VTiger CRM. Results of this research are in the form of new business process modeling, implementation using VTiger CRM, and recapitulation of technology acceptance questionnaires from company employees. Speciafically for the questionnaire, an additional module was developed because the module was not available in VTiger CRM.